Formation of Moral and Ethical Values in Students of the New Ukrainian School Based on the Use of Innovative Technologies - Kopchuk-Kashetska, Mariia (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
At the present stage of creation of Ukraine as a democratic, legal state and its integration into the European community, the problem of forming moral and ethical values in students of the New Ukrainian school based on the use of innovative technologies is becoming more relevant. The effects of political and moral crises, globalization of society and detachment of the younger generation from national background, replacement of universal moral and ethical values by the youth subculture are becoming increasingly apparent. This encourages the use of innovative learning technologies at primary school lessons, the best ways of moral and ethical education of students based on various exercises, games and more. The centuries-old experience of the life of the Ukrainian people, its ideals, ideas of good and evil, sublime and ugly are concentrated in moral and ethical values. The educational rate of moral and ethical values is that they are also the result of the practice of educating the younger generation. It is convincingly proved that the acceleration of the pace of life, a large flow of knowledge affects modern people, requires the ability to find the necessary solution quickly, using search methods and many different sources of information in this regard, among traditional forms and methods of teaching, innovative pedagogical technologies are increasingly used in pedagogical practice. The article reveals the problem of formation of moral and ethical values in students of the new Ukrainian school based on the use of innovative technologies, theoretically substantiates and proves the feasibility of their use in primary school. The article describes the technologies that primary school teachers are successfully working on. The advantages of these technologies are revealed, their significance, essence and tasks are discussed.